Association Between Insurance Status and Chondrosarcoma Stage at Diagnosis in the United States: Implications for Detection and Outcomes. Issue 4 (15th February 2023) - Yatham, Puja; Garcia, Jacklyn; Fagundo, Valeria; Castro, Grettel; Rodriguez de la Vega, Pura; Ruiz, Juan G.; Belzarena, Ana Cecilia
Abstract : Introduction: Chondrosarcoma is a common primary bone tumor, and survival is highly influenced by stage at diagnosis. Early detection is paramount to improve outcomes. The aim of this study is to analyze the association between insurance status and stage of chondrosarcoma at the time of diagnosis. Methods: A comparative cross-sectional study was conducted using the Surveillance, Epidemiology and End Results database. Patients with a diagnosis of chondrosarcoma between 2007 and 2016 were included. Exposure variable was insurance status and the outcome chondrosarcoma staging at the time of diagnosis. Control variables included tumor grade, age, sex, race, ethnicity, marital status, place of residence, and primary site. Both unadjusted and adjusted (multiple logistic regression) odds ratios (ORs) and 95% confidence intervals (CIs) were computed to estimate the association between insurance status and stage. Results: An effective sample of 2, 187 patients was included for analysis. In total, 1824 (83%) patients had health insurance (nonspecified), 277 (13%) had Medicaid, and the remaining 86 (4%) had no insurance. Regarding stage at diagnosis, 1, 213 (55%) had localized disease, whereas 974 (45%) had a later stage at presentation. Before adjustment, the odds of being diagnosed at an advanced (regional/distant) stage were 55% higher in patients without insurance (unadjusted OR 1.55; 95% CI 1.003 to 2.39). After adjusting for potential confounders, the odds increased (adjusted OR 1.94; 95% CI 1.12 to 3.32). Variables with a significant association with a later stage at diagnosis included older age ( P < 0.001), male sex ( P < 0.001), pelvic location ( P < 0.001), and high grade ( P < 0.001). Conclusion: Being uninsured in the United States increased the odds of a late-stage diagnosis of chondrosarcoma by 94% when compared with insured patients. Lack of medical insurance presumably leads to diminished access to necessary diagnostic testing, which results in a more advanced stage at diagnosis and ultimately a worse prognosis. Efforts are required to remediate healthcare access disparities. Level of Evidence: Level III